Developing Promotion Strategy on Instagram for Lip Glaze Launch by SkinCrave Company - Maghfirah, Nawwal; Qastharin, Annisa Rahmani (Proceedings International Conference on Education Innovation and Social Science, 2023)
SkinCrave exists in the growing skincare market in Indonesia as a clean beauty skincare brand that emphasizes transparency and inclusivity. In order to embody the inclusivity value, SkinCrave aimed to develop skincare products for women with sensitive skin. However, it was found that 80% of the sensitive skin market is selective on purchasing their product and 90% of SkinCrave’s product online sales came from the owner’s personal effort reaching out the network to buy the product, leaving SkinCrave short in inbound sales. Therefore, a good promotional strategy is needed to drive the sales of lip glaze, the upcoming SkinCrave product. The social media strategic framework by Tracy L. Tuten and Michael R. Solomon serves as the guiding framework for the methodology of this study. Interviews were conducted with 8 women from Generation Z who have sensitive skin. Then, the data was analyzed through thematic analysis using NVIVO program. The findings shows that the sensitive skin persona of SkinCrave possesses a careful approach before purchasing skincare products as they seek in depth information and testimonials from their peers, this serves as a foundation of understanding and formulating the best promotion strategy for lip glaze launch. These findings are then applied to the proposed promotion strategy on Instagram for SkinCrave’s lip glaze launch including the timeline and evaluation plan consisting of various touch points from awareness to action. From the result, this research contributes to the understanding of creating promotion strategies specifically for skincare companies whose market is women with sensitive skin.